2003
DOI: 10.1002/bit.10580
|View full text |Cite
|
Sign up to set email alerts
|

Ester synthesis from trimethylammonium alcohols in dry organic media catalyzed by immobilized Candida antarctica lipase B

Abstract: Twenty-one different organic solvents were assayed as possible reaction media for the synthesis of butyryl esters from trimethylammonium alcohols in dry conditions catalyzed by immobilized Candida antarctica lipase B. The reactions were carried out following a transesterification kinetic approach, using choline and L-carnitine as primary and secondary trimethylammonium alcohols, respectively, and vinyl butyrate as acyl donor. The synthetic activity of the enzyme was strictly dependent on the water content, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 20 publications
(18 reference statements)
1
15
0
1
Order By: Relevance
“…In addition, our results show that there was no esterification in all cases when hexane was used as the reaction media because of the low solubility of L-carnitine in hexane. The same phenomenon has been observed for lipase-catalyzed synthesis of butyryl-Lcarnitine [16]. Obtained results coincide well with the higher conversion in solvent-free system, including catalyzed by all three lipases, than in solvents.…”
Section: Selection Of Lipasesupporting
confidence: 76%
See 1 more Smart Citation
“…In addition, our results show that there was no esterification in all cases when hexane was used as the reaction media because of the low solubility of L-carnitine in hexane. The same phenomenon has been observed for lipase-catalyzed synthesis of butyryl-Lcarnitine [16]. Obtained results coincide well with the higher conversion in solvent-free system, including catalyzed by all three lipases, than in solvents.…”
Section: Selection Of Lipasesupporting
confidence: 76%
“…It is known that the solubility of L-carnitine reduced as the Log P parameter of the solvent increased. Pedro et al [16] reported that acetonitrile was the best solvent for lipase-catalyzed synthesis of butyryl-L-carnitine in 21 different solvents. In the case of the lipase-catalyzed synthesis of CLA with phytosterol, the high yield of the reaction in hexane was obtained by Phuong et al [17].…”
Section: Selection Of Lipasementioning
confidence: 99%
“…This method, which represents conversion of primarily one of the two enantiomers of a racemic substrate yielding either the substrate or the product in high enantiomeric purity, is attractive for production of chiral building blocks for pharmaceutical, agricultural, and fine-chemical industry. Lipases are the preferred enzymes for this conversion, as they show activity in nearly pure organic solvents as well as long-term stability (Turner and Vulfson, 2000;Lozano et al, 2003). In particular, Candida antarctica lipase B (CAL-B) is a much used biocatalyst due to its broad substrate specificity and good enantioselectivity (Anderson et al, 1998;Otto et al, 2000;Resnick et al, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…It is accomplished industrially by heating a mixture of the anhydrous esters and alcohols at relatively high temperatures or using alkali metals or alkali alkylates at lower temperatures. The use of lipases can offer the advantages of mild conditions, reduced side reactions, and specificity to the transesterification process (Zaks and Klibanov, 1985;Breslow, 1986;Goldberg, 1989;Gotor, 2002;Lozano et al, 2003); however, the drawbacks of the extensive use of lipases and biocatalysts in general compared with classical chemical catalysts are the instability of enzymes in organic solvents as well as the high cost. Consequently, there is an urgent need for the development of enzyme mimics which are superior to native enzymes in stability, cost and reusability (Breslow, 1982;Murakami, 1992;Descours et al, 2002;Yang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%